2020
DOI: 10.1063/5.0027789
|View full text |Cite
|
Sign up to set email alerts
|

Space charge profile study of AlGaN-based p-type distributed polarization doped claddings without impurity doping for UV-C laser diodes

Abstract: The space charge density profile of the nondoped AlGaN-based p-type cladding layer for UV-C laser diodes realized by distributed polarization doping is examined theoretically and experimentally. The analysis of the capacitance-voltage measurement revealed that the average effective acceptor density of 4.2 × 1017 cm–3 is achieved even without impurity doping, and it is in good agreement with the theoretical prediction from the measured Al composition profile. This result suggests that the cladding layer is idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…These leaked electrons may then recombine with the holes in the p-region, which will overcome the injection of holes in active region [ 12 ]. The recent proposed designs have overcome these challenges, which include the superlattice design of last quantum barrier [ 13 ], quaternary superlattice last barrier [ 14 ], double tapered EBL [ 15 ], step doping in waveguide and cladding layer [ 16 ], compositional Al-grading of silicon-doped layers [ 17 ], AlGaN-based polarization doped layers without impurity doping [ 18 ], step-graded quantum barriers with graded EBL [ 19 ] and inverse trapezoidal EBL [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These leaked electrons may then recombine with the holes in the p-region, which will overcome the injection of holes in active region [ 12 ]. The recent proposed designs have overcome these challenges, which include the superlattice design of last quantum barrier [ 13 ], quaternary superlattice last barrier [ 14 ], double tapered EBL [ 15 ], step doping in waveguide and cladding layer [ 16 ], compositional Al-grading of silicon-doped layers [ 17 ], AlGaN-based polarization doped layers without impurity doping [ 18 ], step-graded quantum barriers with graded EBL [ 19 ] and inverse trapezoidal EBL [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…10) To realize the p-type graded AlGaN, the Mg impurity is not required for all case, but is critical for specific cases to improve electrical conductivity in vertical devices. [13][14][15][16][17][18][19] Recently, Yan et al achieved the hole concentration as high as 9.0 × 10 17 cm −3 in blue light-emitting diodes (LEDs) by optimizing the Cp 2 Mg flow during the growth of graded Al x Ga 1−x N (0 ⩽ x ⩽ 0.3). 15) Yasuda et al reported the type of generated carriers is changed from hole to electron when a lattice relaxation occurs during growth of Al x Ga 1−x N (0 ⩽ x ⩽ 0.2).…”
mentioning
confidence: 99%
“…14) Another Zhang et al reported the high hole concentration in the graded Al x Ga 1−x N (0.73 ⩽ x ⩽ 1) without the Mg dopant. 17) Typically, two types of cladding layers, i.e. the graded Al x Ga 1−x N (0 ⩽ x ⩽ 0.9) layer with and without Mg dopant, are widely employed to realize UVB and UVC LDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1) Development of short-wavelength LDs based on AlGaN materials has been pursued for years. Recently, room-temperature, pulsed lasing in UV-C 2,3) and UV-B 4) wavelength regions has been realized by improving the crystal quality of AlGaN and realizing a high hole concentration and low light absorption in the p-type cladding layer 5,6) by utilizing distributed polarization doping. 7,8) However, continuous wave lasing, which is desired for these devices to be practical, has not yet been achieved.…”
mentioning
confidence: 99%